Feasibility of rapid gravity filtration and membrane ultrafiltration for the removal of microplastics and microlitter in sewage and wastewater from plastic industry. (February 2023) - González-Camejo, J.; Morales, A.; Peña-Lamas, J.; Lafita, C.; Enguídanos, S.; Seco, A.; Martí, N.
Abstract: Wastewater treatment plants (WWTPs) act as barriers in reducing uncontrolled microplastic and microlitter (MP-ML) emissions from both urban and industrial wastewaters. Despite removing most of the MP-ML, large quantities of this waste still enter the environment through WWTP effluents, which means further post-treatment technologies are needed. This study contains a technical evaluation of MP-ML removal from urban wastewater (UWW) and from the wastewater from the recycling plastic industry (PIWW) using two different pilot-scale post-treatment systems: rapid gravity filtration (RGF) and ultrafiltration (UF) membranes. The MP-ML mass concentrations contained in UWW and PIWW were measured by a simplified method adapted for the long-term monitoring of WWTP operations. The method was validated on standard samples. Despite the RGF system consumed less energy than UF treating UWW (0.097 kWh·m −3 and 0.156 kWh·m −3, respectively), RGF was not efficient enough to properly decrease the risk of MP-ML emissions (39.5 ± 34.6 % of MP-ML removal). With respect to PIWW, the energy consumption of the UF plant decreased up to 0.059 kWh·m −3 . The combination of RGF and UF technologies was expected to reduce membrane fouling but it did not show significant differences in the mid-term operation. Graphical abstract: Unlabelled Image Highlights: Rapid and membrane filtration were evaluated to remove microplastics from water. MP measurement methodology was adapted for long-term WWTP monitoring. UF membranes were able to remove all microlitter particles higher than 25 μm. Organic content in UWW was probably responsible for higher fouling rates than PIWW. Combination of rapid and membrane filtration did not reduce fouling significantly.